Polyaromatic Hydrocarbon Oxyradical Stability (Journal of Atomic and Molecular Sciences, 2018)
A simple connection is established between aromaticity and overall stabilityof five-ring linear polyaromatic hydrocarbon oxyradicals. A chemically intuitivemodel is developed that exhibits a linear trend between an inexpensive geometric measureof aromaticity and the energetic stability of a model graphene edge with oxygenat different positions. It is believed to be an important step in establishing reactionpathways of soot and graphene oxidation.